Legal and Policy Considerations in Lebanon Related to Proposals for Paraphilic Disorders in World Health Organization's International Classification of Diseases Manual, 11th Version. Issue 3 (14th January 2020) - Makhlouf, Youmna; Kerbage, Hala; Khauli, Nicole; Ramadan, Zeina; Khoury, Brigitte
Abstract: Introduction: The World Health Organization's general assembly, in its last meeting of May 2019, has approved the suggested changes to the International Classification of Diseases manual, 11th version (ICD-11). Some of the proposed recommendations include the revision of "Disorders of Sexual Preference", now called Paraphilic Disorders, currently listed under the International Classification of Diseases-10 Mental and Behavioural Disorders. Aim: This article presents findings on the analysis of the existing laws and policies that are relevant to paraphilic disorders in Lebanon. Methods: A literature review of all official and unofficial documents, reports, and articles published on laws and health policies relevant to paraphilic disorders in Lebanon was conducted, including a thorough review on Lebanese laws on that matter. Moreover, interviews with government representatives, including the Ministry of Public Health, the Ministry of Justice, the Ministry of Social Affairs, representatives of Non-Governmental Organizations working in child protection, and mental health professionals from the private and public sector, were conducted. Main Outcome Measure: Covered are (i) the health system in Lebanon including policies and laws related to mental health care provision and relevance to paraphilic disorders, (ii) the legal framework and the mental health evaluation and treatment in the Lebanese criminal justice system: the case of paraphilic disorders, (iii) adjudication of sex offenders in Lebanon, (iv) criminal responsibility relevant to paraphilic disorders, and (v) the relationship between legal and clinical issues for non–forensic health professionals. Results: The treatment of paraphilic disorders would follow the treatment of all mental health conditions in Lebanon as no specific services for paraphilic disorders are available within these health-care systems. Legally, sexual crimes in Lebanon are not judged according to the individual's urges, fantasies, or state of mind, rather are assessed according to the acts committed by the individual. Therefore, an individual diagnosed with a paraphilic disorder is not culpable of any crime should he not act on this disorder by committing acts that fall under the scope of the penal code. An analysis of sexual acts that qualify as crimes reveals that the element of consent is rarely taken into consideration as most sexual crimes are defined as such with reference to violation of social norms, primarily "morals and public morality." Therefore, a change in the diagnostic classification of mental and behavioral disorders (ICD or Diagnostic and Statistical Manual of Mental Disorders) should not be a factor in their definition. Furthermore, in the course of enforcing criminal sanctions on individuals diagnosed with a mental disorder, the determining factor will be the individual's state of awareness at the time of the act. Psychiatric expertise initiated in that context lacks standardized criteria for diagnosis and is not bound by law to rely on international classifications; it is usually based on nonstructured interviews. Should it be assessed that the individual was fully aware of the consequences of his or her act, the paraphilic disorder diagnosis should not play any role in the sentencing. Clinical implications: Clinicians in Lebanon can now be aware of the legal sanctions that patients with paraphilic disorders may fall under, should criminal acts be committed. Clinicians can also be familiar with the role of mental health disorders in the legal system, specifically with relevance to "awareness" at the time of the criminal act. Moreover, clinicians can freely use the updated diagnoses of paraphilic disorders in the ICD-11, as they form no legal detriments in Lebanon. Strength & Limitations: The interviewing technique used in this study ensured that participants spoke about issues pertinent to their experience and expertise and helped achieve data saturation. Nonetheless, although this is a review, a quality and bias screening tool was not used because of the search mostly pertaining to legal laws and cases instead of research articles. furthermore, no software was used to analyze the qualitative data from the interviews. In addition, some of the documents reviewed were in Arabic, and therefore, some nuances, while translating the essential findings to English, might have been lost in translation. Conclusion: Compared with the ICD-10, the categories and definitions in ICD-11 should not create any additional obstacles nor offer any direct positive consideration, as the diagnostic classifications of mental disorders (ICD or Diagnostic and Statistical Manual of Mental Disorders) are not relevant to the definition of criminal sexual acts in Lebanon.